2016
DOI: 10.1186/s12906-016-1247-1
|View full text |Cite
|
Sign up to set email alerts
|

Clausenidin induces caspase-dependent apoptosis in colon cancer

Abstract: BackgroundClausena excavata Burm.f. is a shrub traditionally used to treat cancer patients in Asia. The main bioactive chemical components of the plant are alkaloids and coumarins. In this study, we isolated clausenidin from the roots of C. excavata to determine its apoptotic effect on the colon cancer (HT-29) cell line.MethodWe examined the effect of clausenidin on cell viability, ROS generation, DNA fragmentation, mitochondrial membrane potential in HT-29 cells. Ultrastructural analysis was conducted for mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Additionally, clausenidin ( Figure 2 ), obtained from the shrub Clausena excavate Burum.f. induced cell cycle arrest of colon cancer at the G0/G1 phase [ 32 ]. Similarly, cycleanine ( Figure 3 ) extracted from Triclisia subcordata Oliv., exerted the same effect as clausenidin on the cell cycle progression and induced G0/G1 immobilization of ovarian cancer cells [ 34 ].…”
Section: Emerging Cytotoxic Alkaloids: Apoptotic Strategmentioning
confidence: 99%
“…Additionally, clausenidin ( Figure 2 ), obtained from the shrub Clausena excavate Burum.f. induced cell cycle arrest of colon cancer at the G0/G1 phase [ 32 ]. Similarly, cycleanine ( Figure 3 ) extracted from Triclisia subcordata Oliv., exerted the same effect as clausenidin on the cell cycle progression and induced G0/G1 immobilization of ovarian cancer cells [ 34 ].…”
Section: Emerging Cytotoxic Alkaloids: Apoptotic Strategmentioning
confidence: 99%
“…The traditional use of Clausena excavata and its compounds for the treatment of cancer is based on Asian folklore that is devoid of scientific evidence. Previous study reported the anti-tumor properties of clausenidin isolated from the root of C. excavata (Waziri et al, 2016). However, the detailed mechanism of anti-cancer cell effect of clausenidin is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The clausenidin was isolated from the fresh roots of Clausena excavata (Voucher number, 2991/16) as described previously (Waziri et al, 2016). The IC50 of the pure clausenidin at 72 h was 13.8 ±2.89 µg/mL (Waziri et al, 2016).…”
Section: Extraction Of Clausenidinmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorectal cancer is the second most common cause of cancer-related deaths; more than 1.4 million patients are diagnosed with colorectal cancer every year. 1 , 2 Tumor invasion and metastasis are the major cause of poor prognosis. 3 Nowadays, therapeutic methods for metastatic colorectal cancer are limited and insufficient.…”
Section: Introductionmentioning
confidence: 99%